If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15x+8=-4x+9
We move all terms to the left:
-15x+8-(-4x+9)=0
We get rid of parentheses
-15x+4x-9+8=0
We add all the numbers together, and all the variables
-11x-1=0
We move all terms containing x to the left, all other terms to the right
-11x=1
x=1/-11
x=-1/11
| x-4.75=3.5 | | −3x−40=-49 | | 6.4+2.1(z-2)=6 | | 3(4x-8=36 | | 7b=4(40+30) | | 2x+4=-20+10x | | -2k-13+13=7k-12+13 | | x+5.6=63 | | r+6/5=5 | | a^2+63^2=65^2 | | 3.60/m=10.8/8.10 | | x+10.8=30 | | 0.404026=10/x | | 7c-7+7=6c-8 | | 2|x+1|+8=-12 | | 8x²-49=0 | | x-1+7x=36 | | 1/3(x+5)2=7 | | $0.16=17.56+5x | | 9y+36=15y | | 13=n/3+8 | | 3x+1=1x+7= | | (2x)^+(2x+2)^=44 | | 13=n3+8 | | 2x+18=1x+12 | | 9-6c=0 | | 6x-1(12+3x)=30+2x | | 5(7-c)=32 | | 2c+8=31 | | 5(x+2)=6x-8 | | (2x)²+(2x+2)²=44 | | • 3X-4y=7 |